Comparative risks of cardiovascular disease events among SLE patients receiving immunosuppressive medications. (28th December 2020) - Choi, May Y; Li, Daniel; Feldman, Candace H; Yoshida, Kazuki; Guan, Hongshu; Kim, Seoyoung C; Everett, Brendan M; Costenbader, Karen H
Abstract: Objectives: SLE patients have elevated cardiovascular disease (CVD) risk, but it is unclear whether this risk is affected by choice of immunosuppressive drug. We compared CVD risks among SLE patients starting MMF, CYC or AZA. Methods: Using Medicaid Analytic eXtract (2000–2012), adult SLE patients starting MMF, CYC or AZA were identified and propensity scores (PS) were estimated for receipt of MMF vs CYC and MMF vs AZA. We examined rates of first CVD event (primary outcome), all-cause mortality, and a composite of first CVD event and all-cause mortality (secondary outcomes). After 1:1 PS-matching, Fine–Gray regression models estimated subdistribution hazard ratios (HRs.d . ) for risk of CVD events. Cox regression models estimated HRs for all-cause mortality. The primary analysis was as-treated; 6- and 12-month intention-to-treat (ITT) analyses were secondary. Results: We studied 680 PS-matched pairs of patients with SLE initiating MMF vs CYC and 1871 pairs initiating MMF vs AZA. Risk of first CVD event was non-significantly reduced for MMF vs CYC [HRs.d 0.72 (95% CI: 0.37, 1.39)] and for MMF vs AZA [HRs.d 0.88 (95% CI: 0.59, 1.32)] groups. In the 12-month ITT, first CVD event risk was lower among MMF than AZA new users [HRs.d 0.68 (95% CI: 0.47, 0.98)]. Conclusion: In this head-to-head PS-matched analysis, CVD event risks among SLE patients starting MMF vs CYC or AZA were not statistically reduced except in one 12-month ITT analysis of MMF vs AZA, suggesting longer-term use may convey benefit. Further studies of potential cardioprotective benefit of MMF are necessary.